DETERMINAN PREDISPOSISI, PEMUNGKIN DAN PENGUAT YANG BERHUBUNGAN DENGAN KEJADIAN SEKS PRANIKAH PADA REMAJA PUTRI - Ida Mariana Sihombing (Akper Kesdam I/Bukit Barisan Padang, 2021)
The high premarital sex among teenagers causes sexually transmitted diseases, unwantedpregnancies, abortions and teenagers drop out of school. The purpose of the study was to prove thePredisposing, Enabling and Reinforcing Determinants Related to the Incidence of Premarital Sex inYoung Women. The research design is cross sectional. A sample of 182 students was taken by randomsampling. Collecting data using a questionnaire. Data analysis was univariate, bivariate,multivariate. Based on the results of the study, premarital sex was at risk of severe 57.7%, 0%unwanted pregnancy, 0% abortion, 0% sexually transmitted diseases, low maternal education 54.9%,low father education 59.9%, low boyfriend education 46, 7%, knowledge is not good 58.8%, violencein dating 44.5%, family income <UMP 1,800,725 53.3%, exposed to information media 69.8%,meeting duration 3x a week 53.8%, parental role is not good 52.2%, family role is not good 41.2%,school role is not good 40.1%, peers are not good 52.7%, parenting pattern is not good 9.3%.Variables related to premarital sex are dating violence, knowledge, family income, school roles,peers, information media. The dominant factor of violence in dating is OR 10,541, 95% CI 4,714-23,570, p-value 0,000, r2 29,2% controlled by school role OR 3,999, 95% CI 1,726-9,267, p-value0,001, r2 3,3 %, controlled by income OR 3.827, 95% CI 1.732-8.458, p-value 0.001, r2 8%,controlled by peers OR 3.890, 95% CI 1.781-8.495, p-value 0.001, r2 8.8% , controlled byinformation media OR 2.869, 95% CI 1.253-6.568, p-value 0.013, r2 5.8%. The conclusion is thatthere are 5 variables that contribute 48.3% to premarital sex in adolescents at SMA N 9 Sijunjung,West Sumatra in 2021.